(untitled) (Global Journal of Human-Social Science, 2011)
Introduction-Malaysians have traditionally apportioned the largest amount of household expenditures on food consumption This item covers consumption of food-at-home FAH and food-away-from-home FAFH Statistics shows that while expenditures on FAH declined steadily from a share of 33 7 to 22 2 between 1973 and 1999 FAFH expenditures rose from 4 6 to 10 9 during the same period Department of Statistics Malaysia 2000 This discernible shift in the mode of food consumption whereby having a meal at home is becoming less often while eating out has become more frequent reflects the changing lifestyle of the Malaysian population